Pharmacogenetics of metamizole-induced agranulocytosis: a systematic review and drug regulation implications - Fidelis, Giovana Fernanda Santos; Dagli-Hernandez, Carolina; Martinelli, Romina P.; Marzuki, Jefman Efendi; Baharuddin, Baharuddin; Yue, Qun-Ying; Edwards, Brian; Pincinato, Eder de Carvalho; Moriel, Patricia (Frontiers in Pharmacology, 2025)
IntroductionMetamizole (dipyrone) is a widely used analgesic and antipyretic, but its use has been restricted in some countries due to the risk of metamizole-induced agranulocytosis (MIA). This systematic review investigated genetic variants associated with MIA, allele frequencies across ancestry groups, and the drug's legal status.MethodsA literature search was conducted across nine databases for studies published up to 08 April 2025. Study selection and data extraction were performed by two independent reviewers. The Withdrawn 2.0 platform was used to assess the global legal status of metamizole, while allele frequencies were obtained from the gnomAD browser (version v4.1.0) and the Allele Frequency Net Database (AFND). Bibliometric analysis was conducted using the VOS viewer software.ResultsIn total, four studies were included in the review. Data related to HLA, NAT2, CYP2C9, CYP2C19, and variants located on chromosome nine were reported; however, statistically significant associations were observed only for variants in chromosome nine and HLA-C*04:01. When comparing countries from different continents with varying metamizole status, the analysis of allele frequencies did not reveal sufficient differences in allele frequencies between countries, which does not justify distinct regulatory frameworks.ConclusionThis study highlights the scarcity of data in the literature reporting the association between genetic variants and MIA. Furthermore, there is insufficient evidence to justify the prohibition of metamizole in certain countries based on genetic variants alone. Additional studies are essential to evaluate the prevalence of MIA, better characterize populations, and explore potential genetic associations, particularly concerning the HLA-C*04:01 allele.Clinical Trial Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024572038, identifier CRD42024572038.